Novel receiver design for suppression of frequency-hopped multiple-access (FHMA) systems - Muhammad Faizal Razali (2019)
Frequency-hopping spread-spectrum has been widely gaining interest due to its commercial and military applications. As there is a demand for growth of wireless communication, it does not allow any room for error. The performance of the Frequency Hopped Multiple Access System is investigated. Various fading systems will be inducted in this report to see how they affect the frequency-hopped multiple access system. Following that we introduce multiple access interference to simulate and study the result of the bit error rate (BER) when multiple users and different number of frequency bands are included. We include five diversity combining techniques and simulate the results in order to study if they help improve the BER of the FHMA system. Based on the Matlab simulations, the addition of diversity combining techniques helps to improve the BER of the system. Although the system gives the best performance under AWGN, we choose to only deal with Rician and Rayleigh fading to simulate the real-life environment where there are multiple scattered paths. We conclude that the clipper receiver technique provides the best BER performance for signal-to-noise ratio for a certain decibel range. The number of frequency hops per symbol also helps in the improvement of the BER. The results also prove that having more frequency hops per symbol helps improve the performance of the system.